Congestion pricing with minimal public opposition: The use of high-occupancy toll lanes and positive incentives in Israel - Galit Cohen-Blankshtain; Hillel Bar-Gera; Yoram Shiftan (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper reports on the Israeli experience with a high-occupancy toll (HOT) lane between Jerusalem and Tel Aviv. It highlights the integration of a park-and-ride service with the HOT lane and the provision of free parking to encourage carpooling. The paper also analyses Israel's pilot "Going Green" programme and how it demonstrates the potential of positive incentives to address congestion.
Keywords: 330; Verkehrsstau; Parken; Anreizregulierung; Israel